Conférence: «Natacha Chetcuti-Osorovitz: Penser les violences de genre et le continuum carcéral: vers une sociologie de l’émancipation» - Chetcuti-Osorovitz, Natacha (2022)
Natacha Chetcuti-Osorovitz anime une séance du Séminaire multidisciplinaire en études féministes "Savoirs, perspectives, approches "(FEM9000, Groupe 041) des professeures Rachel Chagnon et Djemila Carron. 21 février 2022 Dans le cadre de ce séminaire, Natacha Chetcuti-Osorovitz parlera de son rapport aux savoirs minoritaires et de l’enquête dans une visée d’une sociologie de l’émancipation.
Keywords: approches et analyses; carcéral; discipline; fem9000; femmes*; prison; privilèges; ressource en ligne; sciences humaines; sociologie; systèmes d'oppression; thématiques; violences; violences contre les femmes; épistémologie féministe

Gender and extreme metal: Understanding gender relations in the Montreal extreme metal scene with schipper's gender framework - Beauchamp, Caroline (Université Concordia, 2021)
Extreme metal is a masculine space, yet more and more women join in. They face a contradiction: as women, they are expected to adopt feminine behaviours; however, they are part of a subculture that valorizes warrior masculinity. I sought to understand the gender expectations of the Montreal extreme metal scene and interpret the contradictions encountered by women in this scene with the help of Schippers’ (2007) theoretical framework on gender. To do so, I conducted 16 individual interviews with women and men who take part in the scene. This research fills a gap in the literature on gender that derives from Connell and Schippers’ writings and addresses issues that the field of metal studies has brushed over. I found that metal men are the “default” participants in the scene. They are expected to be fine music connoisseurs and even become musicians. In contrast, women’s presence is heterosexualized and attributed to a romantic or sexual interest in metal men. Women are suspected of being “poseuses” or groupies with no real interest in the music until proven otherwise. To become legitimate participants, they have to overcome those expectations and prove that they are worthy of being viewed through the prism of masculinity rather than femininity. They do so by proving their exceptionality through manhood acts and distancing themselves from other women. Despite their gender transgressions, women’s presence does not fundamentally question gender relations but reaffirms the overall primacy of masculinity over femininity.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; anthropologie; approches et analyses; discipline; genre; hétérosexisme; masculinité; montreal; mémoires/thèses; privilèges; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; stéréotypes de genre; systèmes d'oppression; étude qualitative

Are men getting more emotional? Critical sociological perspectives on men, masculinities and emotions - de Boise, Sam; Hearn, Jeff (The Sociological Review, 2017)
Sociological research, influenced by feminist and other critical perspectives, has noted how men’s emotional inexpressiveness was influenced, and supported, by patriarchal privilege. Such approaches have argued that ‘inexpression’ needs to be broken down in order to build gender equality and improve men’s own wellbeing. Emerging research has, however, challenged the argument that men are ‘emotionally inexpressive’ on two main premises: that, as a result of feminist critiques, many men now practise ‘softer’ or ‘more emotional’ forms of masculinity; second, that emotions always influence social action and so need to be better incorporated into sociological accounts of men’s behaviour. Yet these approaches entail some conceptual confusion as to what emotions are, how they link to social action and whether men’s emotions are inherently transformative for gender relations. This article first details how emotions and masculinity have been theorized in feminist-inspired approaches. It outlines recent work on emotions, men and masculinities before arguing for an understanding of emotions that engages with both physiologically grounded and postconstructionist debates. It finally suggests incorporating a material-discursive approach to men’s emotions, through feminist work on affect, which is attentive to the political dimensions of ‘increasing emotionality’ in order to contribute to a developing field of sociological research.
Keywords: approches et analyses; discipline; genre; inégalités; masculinité; privilèges; rapports sociaux de sexe; ressource en ligne; sciences humaines; sociologie; systèmes d'oppression; émotions

Contre l'indifférence des privilégiés : à quoi sert le care - Gilligan, Carole; Hochschild, Arlie; Tronto, Joan (Payot, 2013)
Comment résister à l'injustice ? Peut-on vaincre le " capitalisme émotionnel " ? Une éthique du care globale est-elle possible à l'heure des migrations transnationales ? Réunies pour la première fois, trois féministes et pionnières de la théorie et de l'éthique du care, la psychologue Carol Gilligan, la sociologue Arlie Hochschild et la politiste Joan Tronto, apportent leurs éléments de réponse avec, en ligne de mire, une injonction : encourager chacun à prendre ses responsabilités pour agir contre l'indifférence des privilégiés. Un événement intellectuel.
Keywords: approches et analyses; care; discipline; division sexuelle du travail; genre; patriarcat; privilèges; psychologie; science politique; science politique et droit; sciences humaines; sociologie; systèmes d'oppression; thématiques; travail; éthique

Geographies of privilege - Twine, France Winddance; Gardener, Bradley (Routledge, 2013)
How are social inequalities experienced, reproduced and challenged in local, global and transnational spaces? What role does the control of space play in distribution of crucial resources and forms of capital (housing, education, pleasure, leisure, social relationships)? The case studies in Geographies of Privilege demonstrate how power operates and is activated within local, national, and global networks. Twine and Gardener have put together a collection that analyzes how the centrality of spaces (domestic, institutional, leisure, educational) are central to the production, maintenance and transformation of inequalities. The collected readings show how power--in the form of economic, social, symbolic, and cultural capital--is employed and experienced. The volume's contributors take the reader to diverse sites, including brothels, blues clubs, dance clubs, elite schools, detention centers, advocacy organizations, and public sidewalks in Canada, Italy, Spain, United Arab Emirates, Mozambique, South Africa, and the United States. Geographies of Privilege is the perfect teaching tool for courses on social problems, race, class and gender in Geography, Sociology and Anthropology.
Keywords: afrique; afrique du sud; amériques; anthropologie; approches et analyses; canada; classe sociale; discipline; environnement; espagne; europe; géographie; italie; mozambique; outils; ouvrages de références; privilèges; racisme; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppression; thématiques; émirats arabes unis; états-unis

Des pratiques d’artistes et de chercheuses en écologie sonore - Piché, Claire (Recherches féministes, 2009)
Cet article propose une incursion dans le domaine de l’écologie sonore à partir d’articles écrits par des artistes et des chercheuses de divers horizons disciplinaires. Après avoir abordé les principes fondamentaux de cette discipline qui a vu le jour durant les années 70, l’auteure présente les pratiques émergentes des femmes en écologie sonore de façon à démontrer ce en quoi leurs façons de faire constituent un terrain propice à la recherche féministe. Le rapport entre l’écologie sonore et le féminisme étant établi, l’auteure expose le sommaire de trois rapports de recherche d’intérêt sociopolitique dont la démarche s’apparente à la recherche-action féministe. Ses réflexions portent ensuite sur les moyens à prendre pour favoriser la collaboration interdisciplinaire.
Keywords: approches et analyses; arts; discipline; femmes* artistes; genre; musique; politique; privilèges; recherche-action; recherche-création; ressource en ligne; science politique et droit; sciences humaines; sociologie; systèmes d'oppression; écologie sonore